Winifred Gérin : biographer of the Brontës - MacEwan, Helen (Sussex Academic Press, 2016)
"The biographer Winifred Gérin (1901-81), who wrote the lives of all four Brontë siblings, stumbled on her literary vocation on a visit to Haworth, after a difficult decade following the death of her first husband. On the same visit she met her second husband, a Brontë enthusiast twenty years her junior. Together they turned their backs on London to live within sight of the Parsonage, Gérin believing that full understanding of the Brontës required total immersion in their environment. Gérin's childhood and youth, like the Brontës, was characterised by a cultured home and an intense imaginative life shared with her sister and two brothers, and by family tragedies (the loss of two siblings in early life). Strong cultural influences formed the children's imagination: polyglot parents, French history, the Crystal Palace, Old Vic productions. Winifred's years at Newnham College, Cambridge were enlivened by such eccentric characters as the legendary lecturer Arthur Quiller-Couch ('Q'), Lytton Strachey's sister Pernel, and Bloomsbury's favourite philosopher, G.E. Moore. Her happy life in Paris with her Belgian cellist husband, Eugène Gérin, was brought to an abrupt end by the Second World War, during which the couple had many adventures: fleeing occupied Belgium, saving Jews in Vichy France, and escaping through Spain and Portugal to England, where they did secret war work for the Political Intelligence Department near Bletchley Park. After Eugène's death in 1945 Winifred coped with bereavement by writing poetry and plays until discovering her true literary metier on her visit to Haworth"-- Provided by publisher.
Keywords: Gérin, Winifred.; Brontë family.; Brontë (Famille); Brontë family; Gérin, Winifred; Women biographers -- Great Britain -- Biography.; Biography as a literary form.; Biography.; Biographies as Topic.; Femmes biographes -- Grande-Bretagne -- Biographies.; Biographie (Genre littéraire); Biographies.; biographies (literary genre); biography (general genre); BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Biography as a literary form; Women biographers; Great Britain; Biography; Biographies